Indian Foreign Policy - "Pant, Harsh V." (New Delhi, 2016)
As India has risen economically and militarily in recent years, its political influence on the global stage has also seen a commensurate increase. From the peripheries of international affairs, India is now at the centre of major power politics. It is viewed as a major balancer in the Asia-Pacific, a democracy that can be a key ally of the West in countering China, even as India continues to challenge the West on a range of issues. This book provides an overview of Indian foreign policy as it has evolved in recent times, it focuses on the twenty-first century and provides historical context for the issues examined. It analyses and discusses India's relationships with both major global powers; the US, China, Russia and the EU, and its neighbouring countries; Pakistan, Bangladesh, Nepal and Sri Lanka. India's policies regarding regions such as East Asia, Central Asia and the Middle East are also considered along with India's role in key global issues such as international and regional organizations, nuclear proliferation, democracy, climate change and trade. With a gradual accretion in its powers, India has become more aggressive in the pursuit of its interests, thereby emerging as an important player in the shaping of the global order in the new millennium. -- .
Keywords: International Politics